Metabolic control from the endolysosome: lysosome-resident amino acid transporters open novel therapeutic possibilities - Kobayashi, Toshihiko; Toyama-Sorimachi, Noriko (Frontiers in Immunology, 2023)
Amino acid transporters are generally recognized as machinery that transport amino acids from the extracellular environment into the cytoplasm. Although their primary function is the uptake of amino acids to supply the cell with nutrients and energy, endolysosome-resident amino acid (EL-aa) transporters possess several unique functions in accordance with their localization in intracellular vesicular membranes. They play pivotal roles in the maintenance of metabolic homeostasis via direct involvement in the amino acid sensing pathway, which regulates the activity of mechanistic target of rapamycin complex 1 (mTORC1), a master regulator of cellular metabolism. Additionally, some EL-aa transporters contribute to the maintenance of dynamic homeostasis of endolysosomes, including the regulation of endolysosomal acidity, by carrying amino acids out of endolysosomes. In addition, EL-aa transporters act as a scaffold to gather signaling molecules and multiple enzymes to control cellular metabolism on the endolysosomal membrane. Among EL-aa transporters, solute carrier family 15 member 4 (SLC15A4) is preferentially expressed in immune cells, including macrophages, dendritic cells, and B cells, and plays a key role in the integration of metabolic and inflammatory signals. In this review, we summarize our recent findings on EL-aa transporter contributions to inflammatory and metabolic signaling in the endolysosomes of immune cells by focusing on the SLC15 family, including SLC15A4 and SLC15A3, and discuss their uniqueness and universality. We also discuss the potential of targeting these EL-aa transporters in immune cells for the development of novel therapeutic strategies for inflammatory diseases. Because these transporters are highly expressed in immune cells and significantly alter the functions of immune cells, targeting them would provide a great advantage in ensuring a wide safety margin.